2014
DOI: 10.1080/00423114.2014.952643
|View full text |Cite
|
Sign up to set email alerts
|

Integration of vehicle yaw stabilisation and rollover prevention through nonlinear hierarchical control allocation

Abstract: This work presents an approach to rollover prevention that takes advantage of the modular structure and optimisation properties of the control allocation paradigm. It eliminates the need for a stabilising roll controller by introducing rollover prevention as a constraint on the control allocation problem. The major advantage of this approach is the control authority margin that remains with a high-level controller even during interventions for rollover prevention. In this work, the high-level control is assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…(8), we obtain: The point representing the centre of the universal joint that connects the bar 3 to the actuator 3 (point B 3 ), and the point that represents the centre of the spherical joint that connects the bar 3 to the end-effector (point A 3 ) are obtained by Eqs. (13) and 14, respectively ( Fig. 4b):…”
Section: Kinematic Modellingmentioning
confidence: 98%
See 1 more Smart Citation
“…(8), we obtain: The point representing the centre of the universal joint that connects the bar 3 to the actuator 3 (point B 3 ), and the point that represents the centre of the spherical joint that connects the bar 3 to the end-effector (point A 3 ) are obtained by Eqs. (13) and 14, respectively ( Fig. 4b):…”
Section: Kinematic Modellingmentioning
confidence: 98%
“…Although the ESP is really effective for vehicle stability control and mitigate rollover situations, other means of control, so as active suspension [2][3][4], active steering [5,6] and active camber [7,8], can contribute to vehicle stability control. Furthermore, many studies have shown that nowadays there is a tendency to integrate two or more technologies to achieve stability control [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review and previous study, there exist some conflicts between roll and yaw stability control in some conditions. 27 The vehicle lateral stability control can be realized through two main approaches. The first one is the suspension control approach, it utilizes active or semi-active components or interconnected configurations to control the vehicle’s posture and load distribution among tires to control its yaw motions.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the braking system control, the variable torque distribution (VTD) system and all-wheel-drive (AWD) technology that effectively control the torque distribution among the wheels are the common choices. 2 However, the braking/traction control systems have their limitations in preventing rollover, 27 because it is too aggressive that a sudden braking action could successfully prevent rollover regarding yaw dynamics and destabilize the yaw motion. There are lots of investigations and applications in terms of the braking/traction control approach in academic study and industry, but it is hard to achieve the performance enhancement in both lateral and roll motion.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Electronic Stability Control systems (ESC) have been originally introduced to stabilize the yaw motion and to prevent over or under steering accidents of modern road vehicles [1][2][3][4][5]. On the other hand, according to the control action, several active rollover prevention systems were proposed such as differential-braking [6][7][8][9][10][11][12], active front wheel steering [13], anti-roll bars [14,15] and active suspension [16,17] or an integration of different actuators [18][19][20][21]. The majority of approaches quantifies the rollover threat by an appropriate index and switches the control authority to a roll stabilizing controller when indicated.…”
Section: Introductionmentioning
confidence: 99%